River networks - Jarvis, Richard S. ;Woldenberg, Michael J. (Stroudsburg, Pennsylvannia : Hutchinson Ross Publishing Company, 1984)
This volume presents key papers in fluvial network analysis. All but one were published after 1945, the date of Robert E. Horton's classic article. During the two subsequent decades, work on fluvial networks followed the Horton-Strahler tradition and developed the morphometric approach. Horton's geometric series laws described river networks with simple equations, which had a profound effect when presented as graphs. However, the graphs gave a false impression of precision; much information was lost in averaging network properties over stream orders. Horton had also attempted to relate his laws to hydrophysical processes and space filling. These goals have been only partially achieved. Because of the shortcomings of the Hortonian approach, the link-based probabilistic approach introduced by Ronald L. Shreve has achieved considerable acceptance. The precise characterization of the network is better preserved using link-based measures, and several investigators have shown that Horton's laws could be generated by probabilistic means, bypassing physical and spatial considerations. Subsequent developments of the link-based approach have led to an increased understanding of the impact of environmental and spatial constraints on network topology and metrics.
Hortons's Law of Drainage Composition -- The Random Model of Drainage Composition -- River Networks and Drainage Basin Geomorphology.
Includes index.
Keywords: GEOMORPHOLOGY